2012
DOI: 10.1007/s00402-012-1661-x
|View full text |Cite
|
Sign up to set email alerts
|

Medial placement of the acetabular component in an alumina-on-alumina total hip arthroplasty: a comparative study with propensity score matching

Abstract: Thin acetabular medial wall and a small inclination angle of the cup were the correlating factors of medial placement of the cup in patients who underwent an alumina-on-alumina THA. Medial placement did not lead to differences in the clinical or radiological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Medializing the acetabular cup on the other hand will allow for a larger femoral offset, less joint loading, and therefore reduced wear 3049. This strategy can be useful in case of gluteal muscle insufficiency as well as to allow for a horizontal cup placement while maintaining sufficient bone coverage 4550. Moving the cup superiorly has been shown to increase joint loading by 0.1% for every millimeter of superior displacement of the hip center of rotation, which is however seven times lower than the 0.7% increase/mm when lateralizing the center of rotation of the hip joint 51…”
Section: The Acetabular Componentmentioning
confidence: 99%
“…Medializing the acetabular cup on the other hand will allow for a larger femoral offset, less joint loading, and therefore reduced wear 3049. This strategy can be useful in case of gluteal muscle insufficiency as well as to allow for a horizontal cup placement while maintaining sufficient bone coverage 4550. Moving the cup superiorly has been shown to increase joint loading by 0.1% for every millimeter of superior displacement of the hip center of rotation, which is however seven times lower than the 0.7% increase/mm when lateralizing the center of rotation of the hip joint 51…”
Section: The Acetabular Componentmentioning
confidence: 99%
“…Two main reasons for the worse outcome were as follows: (1) insufficient coverage of metal shell due to defective acetabulum and (2) difficult cup positioning due to posttraumatic deformity of the acetabulum. 5,6,8 However, we used medialization technique to obtain sufficient acetabular coverage in patients with deficient acetabulum, 13,14 and we performed preoperative CT scan for accurate positioning of acetabular cup. 12 In our study, the results of THA due to posttraumatic arthritis were comparable with those due to osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, we used medialization technique to obtain sufficient acetabular coverage in patients with deficient acetabulum, 13,14 and we performed preoperative CT scan for accurate positioning of acetabular cup. 12 In our study, the results of THA due to posttraumatic arthritis were comparable with those due to osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current techniques for acetabular reconstruction are as follows: standard or custom-made metal augments, roof reconstruction with vascularized fibula or pedicled iliac graft, autologous or homologous bone, reinforcement rings, cranial positioning of the acetabulum, medial protrusion techniques (cotyloplasty) [2]. It has been reported that an 80% intact bone coverage is required for a stable acetabular reconstruction [18,19]. However, 30-40% uncovarage was reported acceptable in other studies [2,5].…”
Section: Discussionmentioning
confidence: 99%